Precipitates in aluminium alloys. Issue 1 (1st January 2018) - Andersen, Sigmund J.; Marioara, Calin D.; Friis, Jesper; Wenner, Sigurd; Holmestad, Randi
ABSTRACT: Precipitation strengthening is a highly complex phenomenon on the nanoscale, responsible for providing strength in Al-Cu, Al-Mg-Cu, Al-Mg-Zn and Al-Mg-Si alloys. Advances in methodology, especially high-angle annular dark-field transmission electron microscopy and atomistic calculations provide fundamental insights into the mechanisms behind precipitation. We are beginning to understand how solute elements form precipitates from the Al matrix and how structures relate. Examples are Ω, η ' and η -phases of Al-Cu and Al-Mg-Zn, where solute organizes in similar supercells in the aluminium lattice. In Al-Mg-Si and Al-Mg-Cu, discovery of 1D Guinier–Preston zone aids understanding of precipitation and growth in the two systems. Graphical Abstract: Abbreviation: 1D: one-dimensional, 3D: three-dimensional, Cs – probe: Spherical aberration corrected electron probe, DFT: Density functional theory, eV: Electron volt, FCC: Face centred cubic, FEG: Field emission gun, GP: Guinier-Preston, GPB: Guinier-Preston-Bagaryatsky, HAADF: High angle annular dark-field, ISMEAR: First order Methfessel-Paxton for smearing, NN: Nearest neighbour, Occ: Occupancy, PAW: Projector augmented wave method, PBE: Perdew-Burke-Enzerhof, STEM: Scanning transmission electron microscopy, TEM: Transmission electron microscopy.